Modernitas, Rasionalitas, dan Identitas Keagamaan: Studi atas Kalender Hijriyah Global Tunggal Muhammadiyah - Hardika Saputra (Al-Jinan : Jurnal Studi Islam, 2026)
This study examines the Global Unified Hijri Calendar developed by Muhammadiyah as an expression of modernity understood as a project of scientific rationalization. Previous studies mainly discuss Islamic calendar debates from jurisprudential and astronomical perspectives, with limited sociological analysis of religious authority and collective identity. This research aims to analyze how the global calendar reflects the shift toward rational-legal authority and shapes contemporary Islamic social dynamics in Indonesia. The study employs a Systematic Literature Review by analyzing classical and contemporary literature on modernity, rationalization, and Islamic movements. The findings reveal that the calendar institutionalizes scientific calculation as a new basis of religious legitimacy, strengthens Muhammadiyah’s identity as a progressive Islamic movement, and generates both contestation and symbolic integration among Muslims. The study concludes that the calendar represents a sociological manifestation of modernity that redefines religious authority and communal cohesion.